2018
DOI: 10.1016/j.molliq.2018.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Study of heavy metals biosorption on native and alkali-treated apricot shells and its application in wastewater treatment

Abstract: Locally available apricot (Prunus armeniaca L.) shells classified as a waste product from fruit processing, were alkali activated in order to develop an efficient heavy metal ions sorbent for water purification. To examine the changes occurred after alkali treatment, raw (SH) and modified apricot shells (SHM) were thoroughly characterized in terms of their chemical composition and surface properties. Chemical analysis revealed that alkaline treatment causes the disintegration of hemicellulose (its content decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 60 publications
3
42
0
5
Order By: Relevance
“…It can be concluded that the adsorption for Pb 2+ on mango peel waste occurs mainly through ion exchange mechanism through the replacement of the alkali and alkaline earth metals, with H + protons bound to the carboxylate groups and the constant complexation with -OH groups of polysaccharides components. The CEC of other types of fruit peels (passion fruit peels, citrus peels, apricot peels) is 26.9 meq/100g, 47.3 meq/100g and 29.51 meq/100g respectively [97,99,114]. The high capacities indicated that citrus peel wastes could remove metal ions by ionexchange mechanism.…”
Section: Other Fruits Peel As Adsorbentsmentioning
confidence: 99%
“…It can be concluded that the adsorption for Pb 2+ on mango peel waste occurs mainly through ion exchange mechanism through the replacement of the alkali and alkaline earth metals, with H + protons bound to the carboxylate groups and the constant complexation with -OH groups of polysaccharides components. The CEC of other types of fruit peels (passion fruit peels, citrus peels, apricot peels) is 26.9 meq/100g, 47.3 meq/100g and 29.51 meq/100g respectively [97,99,114]. The high capacities indicated that citrus peel wastes could remove metal ions by ionexchange mechanism.…”
Section: Other Fruits Peel As Adsorbentsmentioning
confidence: 99%
“…The removal of heavy metal ions using these lignocellulosic materials is attributed to the presence of functional groups such as hydroxyl, carboxyl, and amines. In this sense, it is important to identify functional groups in bioadsorbents [33]. The presence of the functional groups responsible for the adsorption of lead ions on the surface of bio-adsorbent materials was performed by Fourier Transformed Infrared Spectroscopy (FTIR); this technique shows bands that indicate different wavelengths which are directly proportional to the radiation energies in the infrared range.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…The effect of temperature on the biosorption of metal ions of Nickel, Chromium, and Lead by Brassica stem was evaluated by varying the temperature from 20-60 °C. An increase in temperature leads to an increase in the rate of adsorption, and gradually viscosity factor of the solution goes down [32,33]. Figure 6 shows the percentage adsorption of 99%, 97%, and 96% for Nickel, Lead and Chromium ions at 60 °C.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…The effect of temperature on the biosorption of metal ions of Nickel, Chromium, and Lead by Brassica stem was evaluated by varying the temperature from 20-60 • C. An increase in temperature leads to an increase in the rate of adsorption, and gradually viscosity factor of the solution goes down [32,33]. Figure 6 shows the percentage adsorption of 99%, 97%, and 96% for Nickel, Lead and Chromium ions at 60 • C. Furthermore, it was found that Ni 2+ is at first point of adsorption than Pb 2+ and then Cr 6+ ; while keeping other optimized conditions constant, e.g., pH 9 of Ni, pH 4 of Pb 2+ , pH 9 of Cr 6+ , with 120 ppm of Ni 2+ , with 1.0 gm of sorbent of Pb 2+ & Ni 2+ , 0.6 gm for Cr 6+ , 50 mL volume, 250 rpm rate and 60 min of time.…”
Section: Effect Of Temperaturementioning
confidence: 99%